Teachers’ Environmental Management Practices for Risk-Inclusive Play in Elementary Schools: A Systematic Review - Dewi Cahyani; Sehan Rifky Arfanaldy (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to explore teachers’ environmental management practices in supporting risk-inclusive play in elementary school settings through a systematic literature review. It examines how teachers manage play environments to balance children’s safety with meaningful developmental opportunities. By synthesizing selected studies, this research highlights the role of teachers as environmental managers who regulate risk through continuous assessment, spatial arrangement, and adaptive supervision. The findings indicate that flexible environmental management practices allow children to engage in manageable challenges that support physical, social, and emotional development. Teachers who move beyond risk avoidance toward risk management create learning environments that encourage autonomy while maintaining appropriate safeguards. The review also reveals that institutional policies, cultural norms, and parental expectations significantly influence how risk-inclusive play is implemented in schools. Supportive school policies and shared understanding among stakeholders strengthen teachers’ confidence in facilitating challenging play experiences. This study contributes to the field of elementary education by positioning environmental management as a pedagogical strategy rather than merely a safety mechanism, offering insights for teacher education and school policy development aimed at fostering balanced and developmentally supportive play environments.